Conservation and architecture of housekeeping genes in the model marine diatom Thalassiosira pseudonana. Issue 4 (24th March 2022) - Li, Zhengke; Zhang, Yong; Li, Wei; Irwin, Andrew J.; Finkel, Zoe V.
Summary: Housekeeping genes (HKGs) are constitutively expressed with low variation across tissues/conditions. They are thought to be highly conserved and fundamental to cellular maintenance, with distinctive genomic features. Here, we identify 1505 HKGs in the unicellular marine diatom Thalassiosira pseudonana based on an RNA‐seq analysis of 232 samples taken under 12 experimental conditions over 0–72 h. We identify promising internal reference genes (IRGs) for T. pseudonana from the most stably expressed HKGs. A comparative analysis indicates < 18% of HKGs in T. pseudonana have orthologs in other eukaryotes, including other diatom species. Contrary to work on human tissues, T. pseudonana HKGs are longer than non‐HKGs, due to elongated introns. More ancient HKGs tend to be shorter than more recent HKGs, and expression levels of HKGs decrease more rapidly with gene length relative to non‐HKGs. Our results indicate that HKGs are highly variable across the tree of life and thus unlikely to be universally fundamental for cellular maintenance. We hypothesize that the distinct genomic features of HKGs of T. pseudonana may be a consequence of selection pressures associated with high expression and low variance across conditions.